Inhibition of Tyrosinase by Mercury Chloride: Spectroscopic and Docking Studies - Chen, Jianmin; Ye, Yaling; Ran, Mengnan; Li, Qinglian; Ruan, Zhipeng; Jin, Nan (Frontiers in Pharmacology, 2020)
Inorganic mercury compounds were used in skin lightening products since ancient times. Although the previous study demonstrated that mercury impeded the transfer of Cu2+ to the apotyrosinase, the direct effects of mercury on tyrosinase is still unclear. In the present study, the mechanism of mercury chloride (HgCl2)-induced inactivation of tyrosinase was firstly investigated. The IC50 values were 29.97 and 77.93 μmol/L for monophenolase and diphenolase, respectively. Kinetic analysis revealed that HgCl2 inhibited tyrosinase activity in an irreversible non-competitive manner. The strong intrinsic fluorescence quenching suggested that the formation of HgCl2-tyrosinase complex induced conformational changes of the enzyme, and HgCl2 had only one single binding site or a single class of binding site on tyrosinase. The molecular docking and further experiments demonstrated that HgCl2 bound to the amino residuals (His) in the catalytic center of tyrosinase. To our knowledge, these findings presented in this paper were the first evidence of the direct interactions between HgCl2 and tyrosinase, which provided a deep understanding of the inhibition mechanism of mercury on tyrosinase and explanation of mercury induced-dysfunction in cellular function.